Achieving Efficient Alkaline Hydrogen Evolution Reaction over a Ni5P4 Catalyst Incorporating Single‐Atomic Ru Sites - He, Qun; Tian, Dong; Jiang, Hongliang; Cao, Dengfeng; Wei, Shiqiang; Liu, Daobin; Song, Pin; Lin, Yue; Song, Li (Advanced materials (Weinheim), 2020)
Developing efficient electrocatalysts for alkaline water electrolysis is central to substantial progress of alkaline hydrogen production. Herein, a Ni5P4 electrocatalyst incorporating single‐atom Ru (Ni5P4‐Ru) is synthesized through the filling of Ru3+ species into the metal vacancies of nickel hydroxides and subsequent phosphorization treatment. Electron paramagnetic resonance spectroscopy, X‐ray‐based measurements, and electron microscopy observations confirm the strong interaction between the nickel‐vacancy defect and Ru cation, resulting in more than 3.83 wt% single‐atom Ru incorporation in the obtained Ni5P4‐Ru. The Ni5P4‐Ru as an alkaline hydrogen evolution reaction catalyst achieves low onset potential of 17 mV and an overpotential of 54 mV at a current density of 10 mA cm‐2 together with a small Tafel slope of 52.0 mV decade‐1 and long‐term stability. Further spectroscopy analyses combined with density functional theory calculations reveal that the doped Ru sites can cause localized structure polarization, which brings the low energy barrier for water dissociation on Ru site and the optimized hydrogen adsorption free energy on the interstitial site, well rationalizing the experimental reactivity. Ni5P4 nanoparticles incorporating single‐atomic Ru are synthesized by a nickel‐vacancy‐assisted method, and meticulous experimental analyses combined with density functional theory calculations confirm that the incorporation of Ru induces localized structural polarization to optimize the catalytic energetics.